The School Counsellor’s Role in Promoting Social Justice for Refugee and Immigrant Children - Stewart, Jan (Canadian Journal of Counselling and Psychotherapy, 2014)
Shifting demographics in Canadian classrooms lead to a call for preparation programs to better prepare counsellors to work more effectively with refugee and immigrant students. School counsellors can play an integral role in transforming current education systems to become inclusive and socially just learning communities that are culturally responsive to the unique needs of children from diverse backgrounds. An adapted version of Brown’s (2004) theoretical framework, based on the tenets of adult learning theory, transformative learning theory, and critical social theory, is proposed as a model to prepare counsellors who are committed to issues of social justice.